Market Upheaval, Fires and What’s Next for the NBN - Gregory, Mark A (Journal of Telecommunications and the Digital Economy, 2020)
Papers in the December 2019 issue of the Journal include discussion on the future of the $51 billion National Broadband Network (NBN), Benefiting from Asia’s Technology Revolution and the relationship between the use of the Darwin-based coastal High Frequency radio service and the development of social capital in the Northern Territory. The Telecommunications Association is hosting public forums on the future of the NBN in 2020 at RMIT University in Melbourne. A recent decision by the Federal Court has cleared the way for the merger of Vodafone Hutchison and TPG to proceed. It is time for more robust telecommunications infrastructure as the recent devastating bushfires found telecommunications services wanting. The Journal welcomes contributions on telecommunications and the digital economy.